Tankens gennembrud: Affekt og percept i Jan Fabres ”Angel of Death” - Løkkegaard, Tue (Peripeti, 2012)
This article analyzes the Belgian director and artist Jan Fabre’s piece Angel of Death to investigate whether the theatre can produce and engage new images of thought. The article uses Gilles Deleuze and Félix Guattari’s concepts affect and percept. Affect and percept constitute blocs of sensations that are independent of a subjective experience. By analyzing body, sound and space in Fabre’s performance, the article concludes that in Fabre’s composition the theatrical unfolding becomes an unfolding of thought, which goes beyond the limit of subjectivity and representation and can open for new potential worlds, sensations and becomings.